AN EMBODIED READING OF EPIPHANIES IN AELIUS ARISTIDES' SACRED TALES. (28th December 2016) - Tagliabue, Aldo
Abstract : This article focuses on the Sacred Tales (henceforth ST ), Aelius Aristides' first-person account of his terrible diseases and subsequent healing brought about by Asclepius, and sheds new light on this text with the help of the notion of embodiment. In recent decades the ST has received a great deal of attention: scholars have offered two main readings of this work, oscillating between the poles of religion and rhetoric. Some have read the ST as an aretalogy while others have emphasised the rhetorical aims of this text and its connection with Second Sophistic literature.